Gambaran Perilaku Self Management Pada Pasien Hipertensi di Puskesmas Cilograng Tahun 2026 - Apriliawati, Risa (Lentera : Jurnal Ilmiah Kesehatan dan Keperawatan, 2026)
Hypertension is one of the chronic disease that has become a public health problem because it can lead to various serious complications if not properly controlled. One of the important factors in controlling hypertension is the patient's ability o perform self management. This study aimed to describe self management among patients with hypertension at Cilograng Public Health Center in 2026. This study population consisted f 369 patients with hypertension, with a sample of 87 respondents selected using a purposive sampling technique. The research instrument used was the Hypertension Self Management Behaviour Questionnaire (HSMBQ), which consists of 40 items. Data wears analyzed with frequency distribution and percentage. The results showed that the overall Self Management of patients with hypertension was in the moderate category (51,7%). Based on the indicators, self integration was in the moderate category (54,)%), self regulation as in the poor category (49,4%), interaction with healthcare professionals and other was in the poor category (48,3%), and adherence to recommended guidelines was in the good category (39,1%). This study indicates that self management among patients with hypertension still requires improvement particularly in the aspect of self regulation and interactions with healthcare professionals.